Differential effects of warming on the complexity and stability of the microbial network in Phragmites australis and Spartina alterniflora wetlands in Yancheng, Jiangsu Province, China - Pei, Lixin; Ye, Siyuan; Xie, Liujuan; Zhou, Pan; He, Lei; Yang, Shixiong; Ding, Xigui; Yuan, Hongming; Dai, Tianjiao; Laws, Edward A. (Frontiers in Microbiology, 2024)
The impact of climate warming on soil microbial communities can significantly influence the global carbon cycle. Coastal wetlands, in particular, are susceptible to changes in soil microbial community structure due to climate warming and the presence of invasive plant species. However, there is limited knowledge about how native and invasive plant wetland soil microbes differ in their response to warming. In this study, we investigated the temporal dynamics of soil microbes (prokaryotes and fungi) under experimental warming in two coastal wetlands dominated by native Phragmites australis (P. australis) and invasive Spartina alterniflora (S. alterniflora). Our research indicated that short-term warming had minimal effects on microbial abundance, diversity, and composition. However, it did accelerate the succession of soil microbial communities, with potentially greater impacts on fungi than prokaryotes. Furthermore, in the S. alterniflora wetland, experimental warming notably increased the complexity and connectivity of the microbial networks. While in the P. australis wetland, it decreased these factors. Analysis of robustness showed that experimental warming stabilized the co-occurrence network of the microbial community in the P. australis wetland, but destabilized it in the S. alterniflora wetland. Additionally, the functional prediction analysis using the Faprotax and FunGuild databases revealed that the S. alterniflora wetland had a higher proportion of saprotrophic fungi and prokaryotic OTUs involved in carbon degradation (p<0.05). With warming treatments, there was an increasing trend in the proportion of prokaryotic OTUs involved in carbon degradation, particularly in the S. alterniflora wetland. Therefore, it is crucial to protect native P. australis wetlands from S. alterniflora invasion to mitigate carbon emissions and preserve the health of coastal wetland ecosystems under future climate warming in China.